2014
DOI: 10.3109/10428194.2014.894188
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal natural killer/T cell lymphomas with extranasal disease in non-endemic regions are disseminated or have nasal primary: a study of 84 cases from India

Abstract: We report a study of 84 extranodal natural killer/T cell lymphomas (ENKTCLs) from India to understand the disease pattern. Sixty-one patients had nasal disease and three had Waldeyer's ring tumors, while 20 had extranasal sites of presentation, namely: cervix (n = 1), oral cavity (n = 3), orbit (n = 3), liver (n = 1), ileum (n = 1), and soft tissue and lymph nodes (n = 9). Staging of patients with extranasal disease revealed that either they had disseminated disease or the nasal mass was missed during the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…However CD3 negative cases have been previously reported. [7] In this present series all cases were positive for CD56 and CD3 except one patient in whom CD3 was negative. EBER was positive in all cases wherever available.…”
Section: Toxicitysupporting
confidence: 51%
See 1 more Smart Citation
“…However CD3 negative cases have been previously reported. [7] In this present series all cases were positive for CD56 and CD3 except one patient in whom CD3 was negative. EBER was positive in all cases wherever available.…”
Section: Toxicitysupporting
confidence: 51%
“…Of the only 2 large series comprising of 37 cases and 84 cases of ENKTCL described from India, only one study has actually documented the ethnicity of the patients with these neoplasms. Almost half of the cases in that study were from western India where as East India (West Bengal/Assam) constituted 20 % of the overall ENKTCL [7,8].…”
Section: Toxicitymentioning
confidence: 86%
“…Lymph node involvement may be seen in ENKTL . Shet et al identified lymph nodes as the primary site in nine of 84 (11%) ENKTL cases analysed by them, which highlights the need for documenting cytological features of ENKTL, as nodal masses are an easily accessible site to perform FNAC.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors of the T lineage are very rare and are mainly represented by the involvement of the eye socket by an extranodal nasal type [18] NK/T-cell lymphoma. In our case series, lymphomas presented themselves as slow-growing, low-density masses causing diplopia and pain.…”
Section: Discussionmentioning
confidence: 99%